(untitled) (Annals of Medical Research, 2023)
Aim: It was aimed to investigate the effectiveness of nutritional counseling services provided in the diabetes and obesity unit of primary health care services for the control of obesity. Materials and Methods: This study is a retrospectively descriptive research. People applied to the diabetes and obesity unit of a District Health Directorate in Istanbul between 01.01.2017-01.04.2022 constitute the population. Analysis about the first application (height, weight, sociodemographics) was made with 3,259 people; weight loss was evaluated within 1,282 people. Mean, standard deviation, median, minimum, maximum values, numbers (n) and percentages (%) were used for descriptive data. The Mann Whitney U was used if the data not normally distributed. Chi-square test was used for categorical variables. Multivariate analysis is made with Cox-regression analysis. Statistical significance level was p<0.05. Results: 2,973 (91.2%) of the participants were women. The median age was 38.0 (15.0-83.0). Height, weight and BMI median values ​​were 158.0 cm (116.0-190.0), 83.6 kg (56.0-160.2), 33.0 kg/m2 (25.0-64.7), respectively. Weight and BMI loss was observed in 90.8% of the patients. The median weight and BMI loss loss were 2.7 kg (-21.40-56.10) and 1.1 kg/m2 (-8.79-22.69). According to univariate analysis, weight loss percentage of 5% and above was significantly higher in those with low educational status, but this significance was not observed in multivariate analysis. Conclusion: Weight loss was achieved 90.8% of the participants. While it is encouraging to benefit from nutritional counseling at a high percentage; it is important to understand the barriers to weight loss for participants who can not benefit.